2020
DOI: 10.3390/cells9061417
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide Profile of the Mouse Retina

Abstract: Phosphoinositides are known to play multiple roles in eukaryotic cells. Although dysregulation of phosphoinositide metabolism in the retina has been reported to cause visual dysfunction in animal models and human patients, our understanding of the phosphoinositide composition of the retina is limited. Here, we report a characterization of the phosphoinositide profile of the mouse retina and an analysis of the subcellular localization of major phosphorylated phosphoinositide forms in light-sensitive photorecept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In photoreceptors, the concentration of PIPs in rod IS and OS is very low at roughly 0.04 mol% (45). Recent measurements with fluorescent phosphoinositide sensors revealed that the majority of PI4P and PI(4,5)P2 rods is present in the IS and cytoplasm surrounding the nuclei (46); the OS also contains a smaller amount of PI4P but no detectable PIP2. The latter is consistent with a direct measurement showing the presence of trace amount of PI4P but not PI(4,5)P2 in isolated bovine outer segments (47)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In photoreceptors, the concentration of PIPs in rod IS and OS is very low at roughly 0.04 mol% (45). Recent measurements with fluorescent phosphoinositide sensors revealed that the majority of PI4P and PI(4,5)P2 rods is present in the IS and cytoplasm surrounding the nuclei (46); the OS also contains a smaller amount of PI4P but no detectable PIP2. The latter is consistent with a direct measurement showing the presence of trace amount of PI4P but not PI(4,5)P2 in isolated bovine outer segments (47)…”
Section: Discussionmentioning
confidence: 99%
“…Isolated mouse eyecups at ages of P8 and P10 were fixed by immersion in fixative (2% glutaraldehyde-1% paraformaldehyde in 0.1M cacodylate buffer, pH 7.4) at 4°C overnight (32, 46). The eyecups were postfixed with 1% osmium tetroxide in 0.1M cacodylate for 1 h, buffer-rinsed, stained en bloc with uranyl acetate, and subsequently dehydrated in an ascending series of methanol solutions.…”
Section: Methodsmentioning
confidence: 99%
“…For a comprehensive review of phosphoinositides in the context of the retina, see (Wensel, 2020 ). Here we will focus on PI4P and PI(4,5)P 2 , the two most abundant phosphoinositides in photoreceptors (Finkelstein et al, 2020 ).…”
Section: Roles Of Phosphoinositides In Protein Enrichment In the Photmentioning
confidence: 99%
“…This is somewhat curious as INPP5E's localization in primary cilia is suggested to rely on the lipid binding chaperone PrBPδ which is also present in photoreceptors and is important for the OS localization of PDE6 and GRK1 (Zhang et al, 2007 ). It could be that another PI 5-phosphatase resides in the photoreceptor cilium in order to maintain low levels of PI(4,5)P 2 and higher levels of PI(4)P. While PI(4)P is seen in both the IS and OS of photoreceptors, PI(4,5)P 2 appears to be mostly excluded from the OS (Finkelstein et al, 2020 ), suggesting photoreceptors possess a mechanism for either enzymatically removing or excluding PI(4)P 2 from the OS, similar to primary cilia. The PI 5-phosphatase ORCL (Oculocerebrorenal syndrome) is mutated in Lowe and Dent syndromes and was shown to localize to the OS of zebrafish photoreceptors (Luo et al, 2012 ).…”
Section: Roles Of Phosphoinositides In Protein Enrichment In the Photmentioning
confidence: 99%
“…Conversely, in C. elegan s neurons and T. brucei , PI(4,5)P2 is enriched in an endocytic membrane domain (periciliary membrane compartment/ciliary pocket), which lies proximal to the TZ ( Demmel et al, 2014 ; Jensen et al, 2015 ; DiTirro et al, 2019 ). In photoreceptors, while PI(4,5)P2 is also largely excluded from the outer segment (OS), which is a modified cilium, PI(4)P localizes to the OS as well as inner segment and perinuclear regions ( Nasuhoglu et al, 2002 ; Finkelstein et al, 2020 ; Figure 2B ). More studies are needed to systematically evaluate PPI composition across all ciliated cell types and to better understand the physiological significance of cell-specific differences in PPI composition and sub-ciliary distribution.…”
Section: Lipid Composition Of the Ciliary Membranementioning
confidence: 99%